A comparative evaluation of the antimicrobial activity of local antiseptics in revision hip arthroplasty. - A. E. Loskutov; A. V. Digtiar; D. A. Stepanskiy (Medičnì Perspektivi)
In our study there is presented information on the research of antagonistic activity of medications octenidine, decamethoxine, dioxydine, myramistin, povidone-iodine, chlorhexidine in standard dosage form and in dilution (1:1 and 1:5) on microorganisms: S. aureus, S. epidermidis, S. haemolitycus, P. aeruginоsa, E. agglomerans, E. coli isolated from patients in revision hip arthroplasty. A considerable bacrteriostatic and bacreticidal activity of investigated medications on microorganisms was shown. The investigation of antagonistic activity of medications was conducted by the “well” method according to methodological guidelines for experimental (pre-clinical) investigation of medicinal productsfor local treatment of purulent wounds. As a solid nutrient solution there was used Mueller-Hinton agar, in which we made cavities with diameter of 8 mm where experimental medications (0,01 ml) were put. As experimental test-cultures there were used main clinical strains of microorganisms (S. aureus, S. epidermidis, S. haemolitycus, P. aeruginоsa, E. agglomerans, E. coli) isolated from patients, receiving treatment in the department of orthopaedics N 2, I.I. Mechnikov regional clinical hospital. 0.9% physiologic saline was used as a control. Chlorhexidine, octenidine, dioxydine, decamethoxine and povidone-iodine undiluted and in dilution 1:1, causebactericidal effect on staphylococcus, in dilution 1:5 – bacteriostatic effect. Myramistin has practically no effect on staphylococcus. Dioxydine and octenidine in initial dilution have a steady bactericidal effect on E. coli and P. aeruginosa and in dilution 1:1 only dioxydine has bactericidal effect. Chlorhexidine and povidone-iodine have bacteriostatic effect on E.coli and P. aeruginosa. In dilution 1:5 only dioxydine has a bactericidal effect on E. coli and P. aeruginosa. For E. agglomerans only dioxydine in standard dosage form and in dilution 1:1 and 1:5 has bactericidal effect 36mm, 33mm and 25 mm accordingly. But octenidine in a standard dosage form has bactericidal effect on E. agglomerans and in dilution 1:1 – bacteriostatic. Other medications have no effect on E. agglomerans. Antimicrobal effect in a standard dosage form on the greatest amount of experimental microorganisms strains wasin octenidine and dioxydine; in dilution 1:1 – in octenidine and dioxydine on enterobacteria, on staphylococci – chlorhexidine, octenidine and dioxydine; in dilution 1:5 – the maximal effect on enterobacteria was in dioxydine and on staphylococci in chlorhexidine.